2013
DOI: 10.1088/0957-4484/24/41/415702
|View full text |Cite
|
Sign up to set email alerts
|

Conducting properties of nearly depleted ZnO nanowire UV sensors fabricated by dielectrophoresis

Abstract: ZnO nanowires (NWs) with different radii (rNW) have been aligned between pre-patterned electrodes using dielectrophoresis (DEP) for the fabrication of high gain UV sensors. The DEP conditions (voltage amplitude and frequency) and electrode material, geometry and size were optimized to enhance the efficiency during the DEP process. To understand the alignment mechanism of the ZnO NWs, the dielectrophoretic force (FDEP) was analyzed as a function of the DEP conditions and NW dimensions. These studies showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
30
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 21 publications
(23 reference statements)
7
30
0
2
Order By: Relevance
“…33 Quantum theory predicts that the increase of the carrier population in the NW increases the transmission probability through a potential barrier. This result agrees with a previous studies on NWs of different diameters, 25 where it is found that the increase of the conductive volume provokes, it is observed that the NW silanization improves the linear characteristic of the contact formed between the NW and the Al electrode mainly due to the increase of the total free charge in the NW, which can benefit the output parameters of ion-gated field-effect transistors.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…33 Quantum theory predicts that the increase of the carrier population in the NW increases the transmission probability through a potential barrier. This result agrees with a previous studies on NWs of different diameters, 25 where it is found that the increase of the conductive volume provokes, it is observed that the NW silanization improves the linear characteristic of the contact formed between the NW and the Al electrode mainly due to the increase of the total free charge in the NW, which can benefit the output parameters of ion-gated field-effect transistors.…”
supporting
confidence: 93%
“…Similar results have been obtained in a previous work, where current levels of devices with the same geometry were demonstrated to be directly related by rNW of the ZnO NW. 25 Therefore, that higher current levels measured in the silanized device (or even higher 18 untreated ZnO NW based devices) are suggested to be a direct consequence of the SCR narrowing, which means an increase of the conductive volume.…”
mentioning
confidence: 99%
“…Under illumination conditions, electron-hole pairs are created by photon absorption, increasing the carrier density in the NW body; band-bending is then reduced and also the depletion width near the NW surface, increasing the NW effective section for conduction. This effect, also found in other semiconductor NW technologies, explains the observed reduction of the device series resistance under illumination and the corresponding increase of the forward current [21]. Figure 11.…”
Section: Photoresponse Of Single Gaas Nw Based Pdssupporting
confidence: 67%
“…In this regard, contactless NW manipulation methods using electromagnetic fields -like dielectrophoresis (DEP)-are usually much softer than mechanical methods such as contact transfer printing or tape peeling, often resulting less destructive. Different assembly methods have been developed to manipulate NWs, including fluidic alignment, roll contact printing [15,16], Langmuir-Blodgett (LB) film deposition technique, drop-casting [17,18], nano-manipulation [19,20], and dielectrophoresis [21][22][23][24][25][26]. Fluidic alignment, roll contact printing transfer, and LB techniques, all offer the ability to align NWs in parallel but do not allow for precise NW placement in functional systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation